Evidence of egg‐laying grounds for critically endangered flapper skate (Dipturus intermedius) off Orkney, UK. Issue 4 (23rd June 2021) - Phillips, Natasha D.; Garbett, Amy; Wise, Daniel; Loca, Sophie L.; Daly, Olivia; Eagling, Lawrence E.; Houghton, Jonathan D. R.; Verhoog, Peter; Thorburn, James; Collins, Patrick C.
Abstract: Essential fish habitats (EFHs) are critical for fish life‐history events, including spawning, breeding, feeding or growth. This study provides evidence of EFHs for the critically endangered flapper skate ( Dipturus intermedius ) in the waters around the Orkney Isles, Scotland, based on citizen‐science observation data. The habitats of potential egg‐laying sites were parametrised as >20 m depth, with boulders or exposed bedrock, in moderate current flow (0.3–2.8 knots) with low sedimentation. This information provides a significant contribution to the understanding of EFHs for flapper skate.